Linking char reactivity to structural and morphological evolution during high pressure pyrolysis of Morupule coal. (November 2020) - Bikane, Kagiso; Yu, Jie; Long, Xiangyi; Paterson, Nigel; Millan, Marcos
Highlights: High pressure lowers total volatile yields during heating up. Repolymerised structures are thermally cracked at high temperatures. Extent of char graphitisation is limited during heating up. Bubble transport is the main transfer phenomenon for the release of volatiles. Gasification reactivity is independent of pyrolysis pressure. Abstract: Understanding the influence of pressure on char physicochemical properties and reactivity during pyrolysis is principal for the design and optimisation of coal gasification technologies. This work investigated the pyrolysis behaviour of Morupule coal at various pressures and temperatures in a high-pressure wire-mesh reactor (HPWMR). The effect of pressure was pronounced at 600 and 800 °C, resulting in lower total volatile yields at higher pressures due to the repolymerisation of volatiles. Although graphitisation was limited during the heating period, an increase in the concentration of ordered structures was observed during holding at 1000 °C. Marked blowholes on the char surface suggested an explosive bubble transport phenomenon during pyrolysis. Chars produced during the ramping period under high pressure showed higher combustion reactivities than their low-pressure counterparts. However, prolonged holding at peak temperature produced chars of similar reactivity, with their CO2 gasification reactivity found to be independent of pyrolysis pressure.